Multi-material adhesively bonded structures: Characterisation and modelling of their rate-dependent performance. (15th August 2020) - Lißner, M.; Erice, B.; Alabort, E.; Thomson, D.; Cui, H.; Kaboglu, C.; Blackman, B.R.K.; Gude, M.; Petrinic, N.
Abstract: The rate-dependent failure response of multi-material adhesive joints for three deformation modes is investigated. A combination of carbon fibre reinforced polymers (CFRP) and titanium alloy Ti-6Al-4V is employed. The experiments provide important information about the failure sequence of a multi-material adhesive joints, which depends upon the loading rate regime. This is the first time that dynamic fracture mechanics experiments are performed in multi-material adhesive structures. The observed experimental results suggest a rate-dependent failure sequence for mode I dominated fracture. Simulations of the experiments are used to predict and rationalise the failure performance of the multi-material adhesive joint. The numerical analysis highlighted the importance of the individual knowledge of the rate-dependent mechanical performance of adhesive and composite to fully understand the fracture sequence of multi-material joints under impact.